Cytotoxic effect of galvanically coupled magnesium‐titanium particles on Escherichia coli. Issue 12 (12th May 2021) - Kim, Jua; Ren, Dacheng; Gilbert, Jeremy L
Abstract: Orthopedic device‐related infections (ODRIs) are difficult to control due to microbial biofilm formation and associated with high‐level resistance to conventional antibiotics. In many cases, the only treatment option for ODRI is explantation. Previous studies have shown that application of cathodic potentials at the metal surface can eradicate biofilms, and Mg and Mg‐Ti particles have the same effect as cathodic potentials. This study investigated the effects of Mg and Mg‐Ti particles on established biofilms and planktonic cells E. coli . Bacterial cultures with developed biofilms or planktonic cells were treated with Mg or Mg‐Ti particles, and the viability were assessed using flow cytometry or visual assessment methods (i.e., observation from SEM images and opacity of the solution). It was found that viability of biofilms treated with 16.67 mg/ml of Mg was 2.8 ± 0.96% at the end of 6‐hr killing compared to untreated controls. This extent of killing was more significant compared to 24‐hr grown biofilms treated with ofloxacin, an antibiotic known to be effective against these bacteria. Biofilms treated with 50 and 100 μg/ml of ofloxacin had 62 ± 4.6% and 52 ± 19.3% survival, respectively, where ofloxacin at these concentrations is known to kill planktonic counterparts very effectively. Inhibition zone tests revealed that biofilms within 2 mm of Mg or Mg‐Ti particle clusters were effectively killed. These results demonstrated the potential of Mg or Mg‐Ti particles in killing microbial biofilms and potential for controlling ODRI.